THE EFFECTS OF MYOFASCIAL SELF-RELEASE METHOD AND TOOL APPLICATION ON ATHLETE STRENGTH INDICATORS IN TIBIA EXTENSOR MUSCLES IN FITNESS - Čupriks, Leonīds; Ķeizāne, Aleksandra; Freibergs, Valts (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The aim of the present study was to analyse the effectiveness of myofascial self-release methods and the use of the tool in the development of strength indicators in the tibia extensor muscles. Instrumental assessment of muscle function was performed on a REV 9000, Technogymᴿ, Italy. The subjects of our study were twenty healthy fitness athletes aged between 20 and 23 years. A set of strength exercises was developed, consisting of 10 exercises focused on increasing the muscle strength of tibia extensor muscles. For the experimental group self-massage with a roller was applied. When applying strength-development exercises with a set of self-release, the dynamics of maximum strength results are as follows: the force balance of the dominant and the non-dominant leg in the control group before (p=0.001) and after (p=0.02) the experiment, and in the experimental group before (p=0.01) and after (p=0.02) the experiment remained unchanged – no significant changes were observed in the results between the groups; - positive dynamics in strength changes were observed for the dominant leg between the control group (p=0.08) and the experimental group (p=0.37) before and after the experiment. The positive increase in the results is in favour of the experimental group, although there are no significant statistical differences in the results of the control group. On the other hand, no differences in the strength dynamics of the non-dominant leg were found.